Assessment of nutritional status and trace element contamination of holm oak woodlands through analyses of leaves and surrounding soils. - De Nicola, F.; Maisto, G.; Alfani, A. (The Science of the total environment, 2003)
The nutritional status and trace element contamination of holm oak woodlands in Vesuvius National Park were assessed by analyses of Quercus ilex L. leaves and surrounding soils. The concentrations of Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, V and Zn were measured in 1-year-old leaves, and in the soils at 0-5 and 15-20 cm depths. The potentially available concentrations were also measured for the soils. The leaf element concentrations were similar to the Q. ilex chemical fingerprint, thus indicating a good nutritional status and the absence of short-term trace element depositions. Total K and V were more abundant in the deep soil layers than in the surface ones, whereas Cd and Pb showed higher values in the surface soils. This suggests that long-term soil accumulations of Cd and Pb are due to atmospheric input. The soil availabilities of Cd, Pb and Zn were high, and Cr availability was very low. A correlation between the available concentrations in the deep soil layers and leaf concentrations was found only for Zn.
The following values have no corresponding Zotero field: accession-num: 12826392
Keywords: Available soil elements; Micro and macro elements; Quercus ilex L.leaves; Total soil elements; Vesuvius National Park

Assessment of nutritional status and trace element contamination of holm oak woodlands through analyses of leaves and surrounding soils. - De Nicola, F; Maisto, G; Alfani, a (The Science of the total environment, 2003)
The nutritional status and trace element contamination of holm oak woodlands in Vesuvius National Park were assessed by analyses of Quercus ilex L. leaves and surrounding soils. The concentrations of Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, V and Zn were measured in 1-year-old leaves, and in the soils at 0-5 and 15-20 cm depths. The potentially available concentrations were also measured for the soils. The leaf element concentrations were similar to the Q. ilex chemical fingerprint, thus indicating a good nutritional status and the absence of short-term trace element depositions. Total K and V were more abundant in the deep soil layers than in the surface ones, whereas Cd and Pb showed higher values in the surface soils. This suggests that long-term soil accumulations of Cd and Pb are due to atmospheric input. The soil availabilities of Cd, Pb and Zn were high, and Cr availability was very low. A correlation between the available concentrations in the deep soil layers and leaf concentrations was found only for Zn.
Keywords: Available soil elements; Micro and macro elements; Quercus ilex L.leaves; Total soil elements; Vesuvius National Park